Comparing the Islamisation of the Jochid and Hülegüid Uluses: Muslim and Christian Perspectives - Roman Hautala (Revue des Mondes Musulmans et de la Méditerranée)
Abstract: Khan Özbek’s rise to power was a pivotal moment in the Islamisation of the Golden Horde nomads. Recently, Russian researchers have shown an increased interest in Özbek’s religious policy and the degree to which Golden Horde nomads were Islamised during his reign. Several researchers argue that Özbek succeeded in completely Islamising his domain at the beginning of his reign. However, this interpretation is largely based on written Islamic sources that should not be taken at face value. Franciscan sources written within the Golden Horde suggest that Islam was not uniformly adopted in the Jochid ulus. A comparison with the neighbouring Ilkhanate at the end of the 13th c. shows that the Mongol rulers achieved relatively limited success in their attempts to forcibly impose Islam on their nomadic subjects.